High resolution imaging of the hippocampus at 7T - Adeyemi, Oluwatobi (2023)
Magnetic Resonance Imaging (MRI) is a powerful medical imaging technique that provides detailed visualization of internal structures in vivo, making it an indispensable tool in diagnosing and monitoring brain-related diseases and pathologies. In this thesis, we focus on the hippocampus, a critical brain region for memory and learning, and investigate its susceptibility, volume, and vascularization using high-resolution MRI at 7T.